Evaluation of perceived stress and resilience among postgraduate academic‐affiliated pharmaceutical industry fellows. Issue 2 (18th January 2023) - Strong, Delaney M.; Amin, Sana; Caputo, Joseph; Heck Sheehan, Amy; Seyss, Carolyn; Mistry, Amee; Miller, Monica L.
Abstract: Introduction: It has been determined that pharmacy residents experience high levels of perceived stress; however, the extent of stress perceived by pharmaceutical industry fellows has not been quantified. This study examined the level of perceived stress academic‐affiliated postgraduate pharmaceutical industry fellows experience, along with identification of what types of stressors they experience, possible factors associated with higher levels of perceived stress, and the state of resilience skills in this population. Methods: A multi‐item survey instrument was created to collect information about fellow demographics, perceived stress using the Perceived Stress Scale (PSS‐10), major stressors, and resilience skills using the brief Connor‐Davidson Resilience Scale (CD‐RISC‐10). Postgraduate year one (PGY1) and postgraduate year two (PGY2) industry‐affiliated pharmaceutical fellows at programs with academic collaborations through Rutgers University Ernest Mario School of Pharmacy, Massachusetts College of Pharmacy and Health Sciences (MCPHS), and Purdue University College of Pharmacy were invited to complete the anonymous survey instrument from March to May 2022. Results: A total of 83 complete responses were received, for a response rate of 21.4%. The mean PSS‐10 score for fellows was 14.8 (SD, 5.7). For resilience, the mean CD‐RISC‐10 score was 29.0 (SD, 5.2). No relationships were found between fellow demographics, perceived stress, and resilience skills. Fellows reported experiencing stress caused by work role/responsibilities (72.3%), personal/physical stressors (68.7%), work environment (37.3%), and home environment (28.9%) in the past month. The top reported coping strategies were exercising/sports (65.1%), spending time with family/friends (48.2%), and watching television (33.7%). Conclusion: Academic‐affiliated pharmaceutical industry fellows reported a moderate level of perceived stress and lower resilience levels than the general population. Results from this research will be used to develop a customized wellness initiative to support pharmaceutical industry fellows.